A comprehensive review of small regulatory RNAs in Brucella spp. - King, Kellie A.; Caudill, Mitchell T.; Caswell, Clayton C. (Frontiers in Veterinary Science, 2022)
Brucella spp. are Gram-negative bacteria that naturally infect a variety of domesticated and wild animals, often resulting in abortions and sterility. Humans exposed to these animals or animal products can also develop debilitating, flu-like disease. The brucellae are intracellular pathogens that reside predominantly within immune cells, typically macrophages, where they replicate in a specialized compartment. This capacity of Brucella to survive and replicate within macrophages is essential to their ability to cause disease. In recent years, several groups have identified and characterized small regulatory RNAs (sRNAs) as critical factors in the control of Brucella physiology within macrophages and overall disease virulence. sRNAs are generally less than 300 nucleotides in length, and these independent sRNA transcripts are encoded either next to (i.e., cis-encoded) or at a distant location to (i.e., trans-encoded) the genes that they regulate. Trans-encoded sRNAs interact with the mRNA transcripts through short stretches of imperfect base pairing that often require the RNA chaperone Hfq to facilitate sRNA-mRNA interaction. In many instances, these sRNA-mRNA interactions inhibit gene expression, usually by occluding the ribosome-binding site (RBS) and/or by decreasing the stability of the mRNA, leading to degradation of the transcript. A number of sRNAs have been predicted and authenticated in Brucella strains, and a variety of approaches, techniques, and means of validation have been employed in these efforts. Nonetheless, some important issues and considerations regarding the study of sRNA regulation in Brucella need to be addressed. For example, the lack of uniform sRNA nomenclature in Brucella has led to difficulty in comparisons of sRNAs across the different Brucella species, and there exist multiple names in the literature for what are functionally the same sRNA. Moreover, even though bona fide sRNAs have been discovered in Brucella, scant functional information is known about the regulatory activities of these sRNAs, or the extent to which these sRNAs are required for the intracellular life and/or host colonization by the brucellae. Therefore, this review summarizes the historical context of Hfq and sRNAs in Brucella; our current understanding of Brucella sRNAs; and some future perspectives and considerations for the field of sRNA biology in the brucellae.